Analisis soal evaluasi pembelajaran tematik semester 1 berdasarkan perspektif HOTS di kelas V sekolah dasar - Wahyu Ary Ramadhani; Chumdari Chumdari; Karsono Karsono (Didaktika Dwija Indria, 2021)
The purpose of this research is to describe the composition of questions and characteristics of HOTS questions in the final assessment of semester 1 of grade five Elementary School 1 Ngepungsari for the 2019/2020 academic year. The method used is descriptive document analysis. The data source is the fifth-grade Semester 1 Final Assessment document. The data collection technique used was document study. Data are analyzed using the Miles and Huberman model. The results of this research indicate that the composition of the HOTS and LOTS items is still not ideal, because the composition of the HOTS and LOTS questions is still not balanced, and the characteristics of the HOTS questions in the Final Assessment items are 43 items. All of the questions had the characteristics of higher-order thinking skills, and 11 of them were also questions that used contextual problem-based characteristics. This research is used to provide teacher knowledge in making final semester assessment questions. This research can also be a theoretical basis for further relevant research. The results of this study can also be used as a solution to the obstacles experienced by the teacher in determining a good composition of questions for the final semester assessment.